Anatomical differences in the human inferior colliculus relate to the perceived valence of musical consonance and dissonance. Issue 7 (16th July 2013) - Fritz, Thomas Hans; Renders, Wiske; Müller, Karsten; Schmude, Paul; Leman, Marc; Turner, Robert; Villringer, Arno
Abstract Helmholtz himself speculated about a role of the cochlea in the perception of musical dissonance. Here we indirectly investigated this issue, assessing the valence judgment of musical stimuli with variable consonance/dissonance and presented diotically (exactly the same dissonant signal was presented to both ears) or dichotically (a consonant signal was presented to each ear – both consonant signals were rhythmically identical but differed by a semitone in pitch). Differences in brain organisation underlying inter‐subject differences in the percept of dichotically presented dissonance were determined with voxel‐based morphometry. Behavioral results showed that diotic dissonant stimuli were perceived as more unpleasant than dichotically presented dissonance, indicating that interactions within the cochlea modulated the valence percept during dissonance. However, the behavioral data also suggested that the dissonance percept did not depend crucially on the cochlea, but also occurred as a result of binaural integration when listening to dichotic dissonance. These results also showed substantial between‐participant variations in the valence response to dichotic dissonance. These differences were in a voxel‐based morphometry analysis related to differences in gray matter density in the inferior colliculus, which strongly substantiated a key role of the inferior colliculus in consonance/dissonance representation in humans.